Modeling and Simulation of the Effect of Airbag Thickness on the Performance of Extended Handle Pneumatic Floor Jack - Aliy, Abduljebar Mahmud; Nallamothu, Ramesh Babu; Nasir, Abdulbasit (Modelling and Simulation in Engineering, 2024)
In the process of changing tires, drivers require a suitable lifting device, namely, a jack, that can be inserted into a designated slot strategically positioned beneath the vehicle. Similarly, in workshops and maintenance facilities, jacks are essential for part replacements and maintenance. This research focuses on the design and analysis of extended handle pneumatic floor jacks specifically tailored for light-duty vehicles. The aim is to enhance effectiveness by enabling the repair of multiple vehicles simultaneously using a single compressor. The study utilizes ANSYS 2022R1 to assess the structural weaknesses of pneumatic airbags, aiming to explore technological advancements and develop an optimal airbag design capable of lifting light vehicles. Natural rubber is utilized as the airbag material, with thicknesses of 2.5 mm, 2.75 mm, and 3 mm. The study investigates three different airbag behaviors: von Mises stress, strain, and deformation in two directions. A pressure of 8.2 MPa is applied, and a weight of 4000 kg is imposed. The results indicate that the 2.5 mm and 2.75 mm thicknesses are unable to sustain the load and pressure, with the weakest area identified between the natural rubber and the metal cast iron that contacts the car’s body. Overall, the research achieved its objectives, and the findings will be effectively applied to model the extended handle pneumatic floor jack, facilitating tire lifting for maintenance and tire changes.